Експертиза проектів нормативно-правових актів у Франції - Мінкова, О. Г.; Minkova, O. H. (Право і безпека. - 2015. - № 1 (56). - С. 29-34., 2015)
Розкрито особливості здійснення експертизи проектів нормативно-правових актів у Франції. Проаналізовано положення французького законодавства, що стосуються експертного забезпечення правотворчості. Досліджено діяльність державних органів Франції з оцінки регулюючого впливу спроектованих норм права.

The object of the study is the examination of the drafts of regulatory acts. The subject of the research is the features ofexpert guarantee oflaw-making activities in France. The article’s objective is to highlight French experience of realizing the expertise of the drafts of regulatory acts that necessitates the analysis of regulatory and institutional components of the expert guaranteeing of law-making in France. The need for achieving the objective of the study has led to the use of dialectical, formal and logical, systematic and comparative methods of cognition. The relevance of the study is the fact that the strategic direction of Ukraine’s legal system development in modern conditions is its entry into the European Union. This requires the system work in using European experience to ensure the quality of legislation. It is established that the necessary legal basis to assess the regulatory impact of the drafts of new regulatory decisions is created in France at the level of national Constitution and laws. The activity of the Committee on the evaluation and control over the public policy, the State Council, the Economic, Social and Environmental Council, the Constitutional Council, administrative authorities with advisory powers is researched. It is proved that the institutionalization of expert assessments contributes counting methodological aspects and requirements of effective legal regulation at the stage of preparation of the law text, creates prerequisites for deepening cooperation between administrative authorities and institutions of civil society in law-making sphere. The practical significance of the work is the fact that grounded provisions and conclusions deepen scientific knowledge about expert guaranteeing of law-making. Obtained results can be used in teaching the theory of state and law and to solve practical problems related to the development and assessment of the drafts of regulatory acts. It is concluded that the experience of expert guaranteeing of law-making in France requires further advanced research aiming at using it in the national law-making activity.

Раскрыты особенности осуществления экспертизы проектов нормативно-правовых актов во Франции. Проанализированы положения французского законодательства, касающиеся экспертного обеспечения правотворчества. Исследована деятельность государственных органов Франции по оценке регулирующего воздействия спроектированных норм права.
Minkova, O.H. (2015), “Examination of the drafts of regulatory acts in France” [“Ekspertyza proektiv normatyvno-pravovykh aktiv u Frantsii”], Pravo i Bezpeka, No. 1, pp. 29–34.
Мінкова, О. Г. Експертиза проектів нормативно-правових актів у Франції // Право і безпека. - 2015. - № 1 (56). - С. 29-34.
Keywords: Конституційне право. Constitutional Law. Конституционное право; Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; регулюючий вплив; evaluation of regulatory impact; законодательство Франции; експертиза нормативно-правових актів; правотворчість; законодавство Франції; expertise; law-making; normative legal act; French legislation; регулирующее воздействие; экспертиза нормативно-правовых актов; правотворчество; Франція; Франция; France